Measuring positive mental health in children with attention-deficit/hyperactive disorder - José Ramón Gómez-Cabezas; Maria Stavraki; Ricardo García-Márquez; Darío Díaz; Miriam Bajo (Scientific Reports)
Abstract Given the importance and prevalence of Attention-Deficit/Hyperactive Disorder (ADHD), numerous studies have focused on relevant psychopathological symptoms. Although ADHD has a negative impact on various core domains of children’s well-being, research regarding the disorder’s effects on positive mental health has been more limited. This pathological view is partial and should be completed with a positive perspective. For this reason, the main objective of the present research is to apply a model that integrates both perspectives, the Two-continua Model of Mental Health, to a sample of children diagnosed with ADHD. As expected, Parallel Analysis and Exploratory Factor Analysis indicated that two different unipolar correlated dimensions emerged from the presence of symptoms of psychopathology (i.e., inattention and hyperactivity/impulsivity) and the presence of symptoms of positive mental health (i.e., hedonic well-being, psychological well-being, and social well-being). ADHD symptoms correlated significantly with psychological and social well-being but not with hedonic well-being indicators. As a conclusion, to accurately assess the mental health of children with ADHD, evaluation protocols should include both psychopathology and well-being measures.